Avaliação do diformiato de potássio sobre o desempenho produtivo e reprodutivo de matrizes de corte - Martins, Patrícia Eick (2005)
The development of new feed additives has improved poultry performance. Potassium Diformate (KD) is one of the most recent product used in the animal production, especially in pork industry, however for poultry few data are available up to now. Two trials were done, with the objective to evaluate KD effect on broiler breeder productive and reproductive performance. The experiments were carried out at the Poultry Science Laboratory, Federal University of Santa Maria, RS, Brazil. For Trial 1, was used Cobb Breeder from 46th to 54th weeks old were used. Second Trial, Ross Breeder was with 41th to 49th weeks old were used. Birds were submitted to diets with increasing levels of KD. The parameters measured with brioler were: body weight, body weight gain, egg production, egg weight and specific gravity, relative weight of egg shell, yolk and albumen. At hatchery, measured parameters were percentage of alive hatched chick, hatchability, day-old chick weight, percentage of first and second grade chick, and embriodiagnosis. With the progeny, body weight, weight gain, feed intake and feed efficiency were recorded. A complete randomized design was used. For Trial 1, three treatments were used (0; 0.15 and 0.30% of KD), with four replicates with 45 female and 5 males per floor pen. For Trial 2, four treatments were used (0; 0.1; 0.2 and 0.3% of KD) with five replicates. Each replicate was composed by 23 females and two males by floor pen. Data were submitted to ANOVA and regression analysis. When statistically different (P< 0.5), Tukey test was used for mean comparison. Based on the current experiments, it can be concluded that KD fed to broiler breeder, resulted in negative effect on hatchery parameters, however positive effect on progeny performance were observed. Doing to the exploratory character of the trials, more research should be done, elucidating KD applicability and mode of action on broiler breeder.